Prophylactic adnexectomy in BRCA1 and BRCA2 gene mutation carriers (а review of literature) - T. A. Shendrikova; K. P. Laktionov; A. I. Vasilenko (Опухоли женской репродуктивной системы)
The development of genetics in the study of predisposition to malignancies, to ovarian and breast cancers in particular, as well as the experi- ence of prophylactic surgery to reduce the risks of these diseases have permitted prophylactic bilateral tube ovariectomy to be used as a main technique in BRCA1 and BRCА2 gene mutation carriers. The purpose of this investigation is to demonstrate key studies in this area.